Urgency Of Halal Certification In Msme Products - Muhammad Heryudanta; Anugerah Windi Apriliani; Kanzul Fawaid; Taris Widyawati (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
UMKM are business institutions that have proven capable of being the engine of the economy and able to withstand various crises, both national and global. Ponorogo has 39,650 UMKM as of 2022. Since the enactment of the JPH Law, MSMEs have faced a new challenge, namely the obligation to have halal certification for every product marketed. However, halal certification is actually a necessity for MSMEs in an effort to develop and advance their business. Because the halal certification owned by UMKM is able to increase buying interest, buying and selling decisions. But still the awareness to take care of halal certification in UMKM is still low. And in Diponorogo there is still very little for halal certification, especially in the village of Senepo, Slahung sub-district. Efforts for Halal certification continue to be carried out by KUA, one of which is collaboration with the government or campuses to disseminate information to the community. The method used in the implementation of our work program is Halal Dissemination and Certification using the ABCD (Asset Based Community-Driven Development) approach. The results of this activity were the participants in the Certification of Understanding related to Halal Products and the importance of the halal label, as well as making Certification for UMKMs in Senepo Village.